Kvaliteten hos charkprodukter efter borttagandet av namnskydd, samt införandet av EU:s köttdefinition - Olsson, Elin (SLU/Dept. of Food Science, 2011)
Until the 1st of January 2003 there were thirteen processed meat products provided with name protection in Sweden. These products had to contain a certain amount of meat and/or a certain amount of fat to be allowed to carry a recognized name. Among these thirteen products, one could find, for example, meat balls (köttbullar), liver pâté (leverpastej), and Falun sausage (Falukorv). While imports of these products started to increase, the system with name protection lost its ability to guarantee a certain quality for all products sold in Sweden and the legislation was removed on December 31st 2002. At the same time, a common definition of meat was adopted in the European Union. Since the 1st of January 2003, meat, when used as an ingredient, is defined the same way in the whole Union. The new definition was quite similar to the old Swedish definition, but some changes had to be made due to this new legislation. In this report, five manufacturers of processed meat products have been interviewed in order to investigate if the former name protected products still contain the same amounts of meat and fat, even though there nowadays is no law to regulate these parameters. The same companies have answered questions concerning the new definition of meat in the European Union and how they have been influenced by this new legislation. To determine how consumers reason when deciding what type of processed meat products to buy, and how they define meat, 18 consumers have been interviewed. Most of the products that used to be name protected still contain a satisfying amount of meat. Some sausages contain more fat than was allowed when they were name protected. The definition of meat within the European Union allows a higher amount of fat in pig meat (25% before 2003, now 30%). As a consequence of this, the manufacturers can use the same amount of meat raw material, but declare a higher meat content on the package. Before the European Union’s common legislation of 2003, meat from the masticatory muscle and the diaphragm was forbidden to use in most of the name protected products. Today these muscle types are included in the European Union’s meat definition and it is hence legal to use in processed meat products.